Structural diversity in early-stage biofilm formation on microplastics depends on environmental medium and polymer properties - Ramsperger, Anja F. R. M.; Stellwag, Anja C.; Caspari, Anja; Fery, Andreas; Lueders, Tillmann; Kress, Holger; Loeder, Martin G. J.; Laforsch, Christian (Water, 2020)
Plastics entering the environment can not only undergo physical degradation and fragmentation processes, but they also tend to be colonized by microorganisms. Microbial colonization and the subsequent biofilm formation on plastics can alter their palatability to organisms and result in a higher ingestion as compared to pristine plastics. To date, the early stage of biofilm formation on plastic materials has not been investigated in context of the environmental medium and polymer properties. We explored the early-stage biofilm formation on polyamide (PA), polyethylene terephthalate (PET), and polyvinyl chloride (PVC) after incubation in freshwater and artificial seawater and categorized the structural diversity on images obtained via scanning electron microscopy. Furthermore, by the measurement of the initial ζ-potential of the plastic materials, we found that PA with the highest negative ζ-potential tended to have the highest structural diversity, followed by PET and PVC after incubation in freshwater. However, PVC with the lowest negative ζ-potential showed the highest structural diversity after incubation in seawater, indicating that the structural diversity is additionally dependent on the incubation medium. Our results give insights into how the incubation medium and polymer properties can influence the early-stage biofilm formation of just recently environmentally exposed microplastics. These differences are responsible for whether organisms may ingest microplastic particles with their food or not.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Biofilm; EPS; Microplastic; Plastic; SEM; ζ-potential